2020
DOI: 10.1016/j.annonc.2020.08.1578
|View full text |Cite
|
Sign up to set email alerts
|

1264P Updated analysis of tislelizumab plus chemotherapy vs chemotherapy alone as first-line treatment of advanced squamous non-small cell lung cancer (SQ NSCLC)

Abstract: Updated analysis of tislelizumab plus chemotherapy vs chemotherapy alone as first-line treatment of advanced squamous non-small cell lung cancer (SQ NSCLC

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…PD-1 inhibitors camrelizumab and sintilimab were approved for non-squamous NSCLC in the first-line setting on June 19th, 2020 and Feb 3rd, 2021 based on CameL study (NCT03134872) [45] , and ORIENT-11 study (NCT03607539) [46] . According to RATIONALE 307 study (NCT03663205), in which the addition of tislelizumab to chemotherapy resulted in an improved PFS than chemotherapy alone for previously untreated squamous NSCLC [47] , tislelizumab was approved on Jan 14th, 2021 by NMPA.…”
Section: Discussionmentioning
confidence: 99%
“…PD-1 inhibitors camrelizumab and sintilimab were approved for non-squamous NSCLC in the first-line setting on June 19th, 2020 and Feb 3rd, 2021 based on CameL study (NCT03134872) [45] , and ORIENT-11 study (NCT03607539) [46] . According to RATIONALE 307 study (NCT03663205), in which the addition of tislelizumab to chemotherapy resulted in an improved PFS than chemotherapy alone for previously untreated squamous NSCLC [47] , tislelizumab was approved on Jan 14th, 2021 by NMPA.…”
Section: Discussionmentioning
confidence: 99%
“…The RATIONALE307 trial showed that carboplatin plus paclitaxel/nab-paclitaxel combined with tislelizumab signi cantly improved the progression-free survival (PFS) of patients with advanced squamous NSCLC compared with chemotherapy alone. More importantly, no relationships were found between clinical response rates and PFS and PD-L1 expression [12]. In this case, the patient with initially unresectable tumor achieved a pCR and received surgical treatment nally, which implied neoadjuvant chemotheraphy combined with tislelizumab may provide an opportunity of radical resection for such patient.…”
Section: Discussionmentioning
confidence: 80%
“…The detail of the search criteria is shown in Table . Eventually, a total of 14 trials 6,8–11,17–25 were included, with 9454 participants enrolled. The detail of the selection process is shown in Figure 1.…”
Section: Resultsmentioning
confidence: 99%